SIOP Ependymoma I: final results, long-term follow-up, and molecular analysis of the trial cohort - a BIOMECA Consortium study - Ritzmann, Timothy A.; Chapman, Rebecca J; Kilday, John-Paul; Thorp, Nicola; Modena, Piergiorgio; Dineen, Robert A; Macarthur, Donald; Mallucci, Conor; Jaspan, Timothy; Pajtler, Kristian Wilfried; Giagnacovo, Marzia; Jacques, Thomas S; et al. (Neuro-Oncology, 2022)
SIOP Ependymoma I was a non-randomised trial assessing event free and overall survival (EFS/OS) of non-metastatic intracranial ependymoma in children aged 3-21 years treated with a staged management strategy. A further aim was to assess the response rate (RR) of subtotally resected (STR) ependymoma to vincristine, etoposide, and cyclophosphamide (VEC). We report final results with 12-year follow-up and post hoc analyses of recently described biomarkers.Seventy-four participants were eligible. Children with gross total resection (GTR) received radiotherapy, whilst those with STR received VEC before radiotherapy. DNA methylation, 1q, hTERT, ReLA, Tenascin-C, H3K27me3, and pAKT status were evaluated.Five- and ten-year EFS was 49.5% and 46.7%, OS was 69.3% and 60.5%. GTR was achieved in 33/74 (44.6%) and associated with improved EFS (P = .003, HR = 2.6, 95% confidence interval (CI) 1.4-5.1). Grade 3 tumours were associated with worse OS (P = .005, HR = 2.8, 95%CI 1.3-5.8). 1q gain and hTERT expression were associated with poorer EFS (P = .003, HR = 2.70, 95%CI 1.49-6.10 and P = .014, HR = 5.8, 95%CI 1.2-28) and H3K27me3 loss with worse OS (P = .003, HR = 4.6, 95%CI 1.5-13.2). Methylation profiles showed expected patterns. 12 participants with STR did not receive chemotherapy; a protocol violation. However, best chemotherapy RR was 65.5% (19/29, 95%CI 45.7-82.1), exceeding the prespecified 45%.Participants with totally resected ependymoma had the best outcomes. RR of STR to VEC exceeded the pre-specified efficacy criterion. However, cases of inaccurate stratification highlighted the need for rapid central review. 1q gain, H3K27me3 loss, and hTERT expression were all associated with poorer survival outcomes.
Gesehen am 08.07.2022